2012
DOI: 10.3141/2293-07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Binder Types on Engineering Properties and Performance of Porous Asphalt Concrete

Abstract: Porous asphalt concrete (PAC) has an open-graded aggregate mixture to yield high air voids; PAC is mainly applied to the surface drainage layer on high-speed trafficked highway pavements. The objective of the study was to investigate the effect of binder types on the engineering properties and field performance of PAC mixtures. Three binder types were selected for a 19-mm nominal maximum aggregate size gradation: conventional asphalt AR-80, polymer-modified asphalt, and high-viscosity asphalt. A series of labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…The results of this research showed that Cellulose Fibers (CF) were more effective than polyester fibers for reducing draindown in PA mixtures [7], but can be more susceptible to the water effect than other types of fibers [9]. The addition of little amounts of CF, between 0.2 and 0.5% by weight of mixture, was recommended for reducing draindown problems [3], augmenting the longterm resistance to raveling and the Indirect Tensile Strength (ITS) of PA mixtures, but sacrificing part of their infiltration capacity [4,7,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this research showed that Cellulose Fibers (CF) were more effective than polyester fibers for reducing draindown in PA mixtures [7], but can be more susceptible to the water effect than other types of fibers [9]. The addition of little amounts of CF, between 0.2 and 0.5% by weight of mixture, was recommended for reducing draindown problems [3], augmenting the longterm resistance to raveling and the Indirect Tensile Strength (ITS) of PA mixtures, but sacrificing part of their infiltration capacity [4,7,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This recommendation is coincident with that included by ASTM for the design of PFC mixtures [44]. In addition, previous studies [45] reported fabrication of PFC mixtures using low penetration-polymer modified-asphalts (i.e., 45 (1/10 mm) in Japan [45], and 48 (1/10 mm) in Taiwan [18]). Several agencies also specified asphalts with penetration values in the range of 50 to 100 (1/10 mm) [23].…”
Section: Mixture Structural Lifementioning
confidence: 82%
“…Compared to the dense-graded HMA mixtures, some limitations of the PFC mixtures are related to: (i) increased (i.e., immediately after construction) initial asphalt film thickness that can reduce the surface friction [18], (ii) tendency to accumulate black ice and freeze faster and longer [19], (iii) winter maintenance (i.e., in freezing conditions) problems [19], and (iv) relatively high construction cost [20]. In addition, limited structural capacity [21] and reduced functional life (i.e., loss of permeability and noise reduction capacity due to AV clogging) [22] had been indicated as disadvantages of the PFC mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Additives like nanosilica were shown to improve the abrasion resistance of the PAM considerably [24]. Natural fibers such as cellulose fibers are among the most commonly used fibers in PAMs as they improve the binder stability [2,25,26,27,28,29,30,31]. For low-temperature crack resistance, glass fibers can be used [32].…”
Section: Introductionmentioning
confidence: 99%
“…The type of binder is an important factor, as a high-viscosity bitumen improves the cohesion of the binder. Meanwhile, polymer-modified bitumen (PMB) improves the adhesion between aggregates and the binder [16,30,37].…”
Section: Introductionmentioning
confidence: 99%